Lagooning and bio-consortium optimisation for secondary level remediation of simulated sugar factory wastewater - Rehman, Abdul (2011)
Sugar factories are a significant source of water pollution, particularly in developing countries such as Pakistan, where the sugar industry is the second largest after tanneries. The wastewater is disposed of untreated to the environment, since traditional wastewater treatment processes are capital-intensive, energy-demanding and complex in operation. The common approach is to use waste stabilization ponds or lagoons mostly operated on complete retention basis.